Heterothermy is associated with reduced fitness in wild rabbits. (31st December 2017) - Maloney, Shane K.; Marsh, Maija K.; McLeod, Steven R.; Fuller, Andrea
Abstract : An increase in variation in the 24 h pattern of body temperature (heterothermy) in mammals can be induced by energy and water deficits. Since performance traits such as growth and reproduction also are impacted by energy and water balance, we investigated whether the characteristics of the body temperature rhythm provide an indication of the reproductive success of an individual. We show that the amplitude of the daily rhythm of body temperature in wild rabbits ( Oryctolagus cuniculus ) prior to breeding is inversely related to the number of pregnancies in the subsequent seven months, while the minimum daily body temperature is positively correlated to the number of pregnancies. Because reproductive output could be predicted from characteristics of the core body temperature rhythm prior to the breeding season, we propose that the pattern of the 24 h body temperature rhythm could provide an index of animal fitness in a given environment.